Group‐2 Innate Lymphoid Cells Promote HCC Progression Through CXCL2‐Neutrophil‐Induced Immunosuppression. Issue 5 (4th October 2021) - Xu, Xingyuan; Ye, Longyun; Zhang, Qi; Shen, Hang; Li, Shanshan; Zhang, Xiaoyu; Ye, Mao; Liang, Tingbo
Abstract : Background and Aims: Due to their inherent characteristics, the function of group‐2 innate lymphoid cells (ILC2s) varies in a context‐dependent manner. ILC2s are involved in certain liver diseases; however, their involvement in HCC is unknown. In the present study, we assessed the role of an HCC‐derived ILC2 population in tumor progression. Approach and Results: Through FACS and single‐cell RNA sequencing, we discovered that ILC2s were highly enriched in human HCC and correlated significantly with tumor recurrence and worse progression‐free survival as well as overall survival in patients. Mass cytometry identified a subset of HCC‐derived ILC2s that had lost the expression of killer cell lectin‐like receptor subfamily G, member 1 (KLRG1). Distinct from their circulating counterparts, these hepatic ILC2s highly expressed CD69 and an array of tissue resident–related genes. Furthermore, reduction of E‐cadherin in tumor cells caused the loss of KLRG1 expression in ILC2s, leading to their increased proliferation and subsequent accumulation in HCC sites. The KLRG1 − ILC2 subset showed elevated production of chemotaxis factors, including C‐X‐C motif chemokine (C‐X‐C motif) ligand (CXCL)‐2 and CXCL8, which in turn recruited neutrophils to form an immunosuppressive microenvironment, leading to tumor progression. Accordingly, restoring KLRG1 in ILC2s, inhibiting CXCL2 in ILC2s, or depleting neutrophils inhibited tumor progression in a murine HCC model. Conclusions: We identified HCC‐associated ILC2s as an immune regulatory cell type that promotes tumor development, suggesting that targeting these ILC2s might lead to new treatments for HCC.